Industrial process control : advances and applications - Kalani, Ghodrat (Butterworth-Heinemann, 2002)
This is a comprehensive, practical, easy-to-read book on process control, covering some of the most important topics in the petrochemical process industry, including Fieldbus, Multiphase Flow Metering, and other recently developed control systems. Drawing from his own experience and successes at such high-profile companies as Brown and Root and Honeywell spanning more than 20 years, the author explains the practical applications of some of the most intricate and complicated control systems that have ever been developed. Compilation of all the best instrumentation and control techniques used in industry today Interesting theoretical content as well as practical topics on planning, integration and application Includes the latest on Fieldbus, Profibus and Multiphase Flow Metering.